A Spirit of Adventure in Retirement: Japanese Baby Boomers and the Ethos of Interdependence - Katrina Louise Moore (Anthropology & Aging, 2017)
Self-reliance has arisen as a key ethic in relation to older persons in Japan. One part of a larger social trend affecting mature societies around the world is the rising emphasis on elders overcoming dependence in favor of a new ethic of independence. This analysis of older persons in Japan opens a window into the gender dynamics of older-person households, and into the discourses about the lack of an independent autonomous identity in old age aside from that in the workplace. Drawing on fieldwork with retirees, I illuminate retired couples’ experiences of and attitudes about retirement, considering the interpersonal dimensions of interdependence and the ways the ethos of self-reliance influences retirees’ lives. In particular, I analyse how the men seek to embody interdependence in relationships with their wives. How do they adjust in relation to their wives’ expectations, and how do they—and their identities—change after they leave the workforce? Central to this process is an expansion in men’s acts of thoughtfulness in relation to their wives.